Spectrographic Characteristics of the Elevation Phonemes on the Pronunciation of Apico-Dental in Surah Al-Fatihah - Siti Marya Ulpah; Mohamad Zaka Al Farisi; Nalahuddin Saleh; Zalfa Tsania Rachman (An Nabighoh Jurnal Pendidikan Dan Pembelajaran Bahasa Arab, 2025)
Correct pronunciation of Qur’anic sounds is crucial, especially for elevation sounds such as  /tˁ/ and /dˁ/. This study analyzes their spectrographic characteristics in Surah Al-Fatiha recitation by non-native Arabic speakers, as Indonesian speakers (Ummi teachers in Bandung), compared to native Arabic speakers. Using a qualitative comparative method with a case study approach, data from four participants (two males and two females) were collected through recording, listening, and transcription. The analysis uses Praat to examine parameters such as duration, fundamental frequency (F0), intensity, and formants. The Findings show Indonesian speakers pronounce /tˁ/ with longer duration, higher F0, and lower intensity; for /dˁ/, they show shorter duration, higher F0, and lower intensity than natives. Male Indonesians resemble native speakers more closely. Gender analysis reveals males have shorter durations and lower F0 than females. Both groups show similar formant patterns despite acoustic differences, indicating phonetic adaptation. These findings contribute to Arabic phonetics education by highlighting specific acoustic features in non-native pronunciation.